Development of Religious Character Through the Implementation of Ta'lim al-Muta'allim - Rozi, Mahmud Fahrur; Sariman, Sariman; Khasanudin, Mohamad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
It is realized that the morals / the character owned by humans can be changed. The character can be good or bad, the educational process influences it, and the interaction of the social, cultural, educational, and natural environments. In the era of digitalization, education has a vital role in bringing changes in people's lives; there are positive and negative influences, negative impacts, and a decrease in the more behavior of effective educational learners. This research uses a descriptive qualitative approach. The primary data sources are the caretaker of Langitan boarding school, the caretaker of the boarding school, and the asatidz of the boarding school. Data collection techniques use participatory observations, structured interviews, and documentation. While the data analysis uses data collection, condensation, presentation of data, and conclusion withdrawal. Implementing the cultivation of santri characters in Pesantren Langitan is as follows: (1). Regius Character Planting Planning through the Study of Kitab Talim Al Mutaalim at Pondok Pesantren Langitan Tuban includes selecting science, teacher selection criteria, choosing friends, and selecting teachers and how to choose knowledge. (2) Implementation of regius character cultivation through the learning of talim al mutaalim in Pesantren Langitan Tuban through the classical system (madrasah), extra-curricular and non-classical (3) Evaluation of regius character cultivation through learning Talim Al Mutaalim book at Pondok Pesantren Langitan Tuban through daily evaluation, semester evaluation, and year-end evaluation.